Analisis Perencanaan Desain Jalur Sepeda di Kota Tegal - Muhammad Yunus; Isradias Mirajhusnita; Fita Ayunina Lathifah; Reza Agy Rivaldi (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2026)
Bicycle transportation in Tegal City faces various challenges. These include infrastructure issues (bike lanes), such as the lack of dedicated lanes for cyclists, the absence of signage for cyclists, and, most importantly, the lack of a map depicting the actual road conditions cyclists will encounter. The proportion of cyclists on roads in Tegal City is approximately 4%–7% compared to other road users, so supporting infrastructure for bicycle transportation on roads in Tegal City is needed. Therefore, there is a need for bicycle lane design planning that prioritizes safety, comfort, and environmental sustainability. The method used was a survey method involving the direct collection of data in the field, specifically a vehicle volume survey using traffic counting techniques and an inventory technique aimed at measuring road capacity. The Level of Service (LOS) values were 0.3 (B) for Jl. AR. Hakim, 0.27 (B) for Jl. P. Diponegoro was 0.27 (B), Jl. KH. Mas Mansyur was 0.15 (A), Jl. Masjid Agung was 0.15 (A), Jl. Pancasila was 0.2 (B), and Jl. KH. Wahid Hasyim and KH Ahmad Dahlan were 0.15 (A). Additionally, the road type on Jl. AR Hakim, Jl. KH Mas Mansyur, Jl. Masjid Agung, Jl. KH. Wahid Hasyim, Jl. Ahmad Dahlan, and Jl. Pancasila was identified as a “Bike Line,” meaning the bicycle lane is located on the roadway itself and is demarcated by road markings, whereas Jl. P. Diponegoro.